Textbook of ophthalmology - Nema, H. V.; Nema, Nitin (Jaypee Brothers Medical Publishers, 2012)
The sixth edition of Textbook of Ophthalmology has been completely revised to include the latest developments in the field. Beginning with an introduction to the anatomy and physiology of the eye, the book discusses different ocular diseases and their treatment. This edition includes new chapters on Cryotherapy and Laser Therapy. Each chapter includes references for further research and 1000 questions and answers help with review and revision. Almost 900 images and illustrations, as well as a DVD enhance learning and understanding.